Capital flows: Catalyst or hindrance to economic takeoffs? - Joshua Aizenman; Vladyslav Sushko (University of California, Santa Cruz Institute for International Economics (SCIIE), 2011)
This paper applies a probit estimation to assess the relationship between economic takeoffs during 1950-2000 and inflows of portfolio debt, portfolio equity, and FDI, controlling for country's stock of short-term external debt and commodity terms of trade. Average level of FDI inflows is associated with a 23 percent higher takeoff probability relative to a zero FDI inflow benchmark, and this effect is highest for the Latin America subsample, with a 65 rise in takeoff probability. Higher stock of short term external debt has been associated with a substantial negative effect on the probability of a takeoff, and the effect of the short terms debt overhang is largest for Latin American countries. Yet, virtually all the takeoffs were associated with a rise in portfolio debt inflows. At the sample mean, inflow of portfolio debt is associated with approximately 25 percent higher probability of a takeoff. In contrast, a one standard deviation increase in equity outflows (inflows) is associated with a 47 percent (17 percent) decline in the probability of a takeoff. A one standard deviation improvement in commodity terms of trade is associated with 28 percent higher takeoff probability.
Keywords: F15; F21; F36; F43; O40; 330; Kapitalmobilität; Kapitalimport; Portfolio-Investition; Direktinvestition; Wirtschaftswachstum; Welt